Direct laser deposition of 410L stainless steel for surface enhancement of ASTM A36 steel - Guo, Yibo (Nanyang Technological University, 2022)
Direct laser deposition (DLD) is a promising technology for improvement of surface property, researchers have been performing many related studies. ASTM A36 steel is a widely applied steel for its economical and mechanical superiority. But this steel cannot undergo severe corrosion and large impact, so improving the surface properties is necessary. 410L stainless steel contains certain percentage of Cr, has outstanding corrosion resistance, hardness, ductility and high-temperature oxidation resistance.